Utility of NSE, ProGRP, VEGFA and CSI in diagnostics of small cell lung cancer patients - Wójcik, Ewa; Stasik, Zofia; Sas-Korczyńska, Beata; Sobolewska, Krystyna; Korzeniowski, Stanisław; Skotnicki, Piotr; Kulpa, Jan Kanty (Contemporary Oncology/Współczesna Onkologia, 2009)
Aim of the study: Assessment of clinical utility of VEGF results, selected tumour markers (NSE and ProGRP), and the cancer serum index (CSI) was performed with respect to their prognostic value in small cell lung cancer (SCLC) patients. Material and methods: The determination of NSE, ProGRP, VEGFA, alpha-1 acid glycoprotein and prealbumin concentrations and platelet counts was carried out before treatment in 72 patients with SCLC (40 with limited and 32 with extensive disease). The same set of parameters was determined in the reference group consisting of healthy persons. The Cancer Serum Index was calculated for each studied person as the ratio of alpha-1 acid glycoprotein to prealbumin. Results: Areas under ROC curves were respectively: for ProGRP: 0.943 ±0.03; NSE: 0.869 ±0.04; CSI: 0.838 ±0.04; VEGFA: 0.713 ±0.05. The relatively highest diagnostic sensitivity was found for ProGRP. The frequency of elevated NSE, VEGF and CSI results were related to the extent of disease, whereas lack of such dependencies was observed for ProGRP. Relationships were found between time of survival and advancement of disease as well as initial values of studied parameters. Extent of disease and higher than discriminant value of ProGRP and VEGFA concentrations count among the independent and unfavourable prognostic factors in SCLC patients. Patients with extensive disease as well as with pre-treatment ProGRP concentrations above 670 ng/l and exceeding VEGFA level 420 ng/ml showed 2.5 times higher risk of death.